ACCEPTABILITY AND UTILIZATION OF GRADED LEVELS OF GMELINA ARBOREA AND CASSAVA PEELS CONCENTRATES IN WEST AFRICAN DWARF SHEEP (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The nutritive value ,voluntary dry matter intake, and the nutrient digestibility of graded levels of Gmelina arborea and cassava peels concentrates in WAD sheep was investigated. Twelve WAD sheep aged 1-2 years old and weighting 14.00± 0.45 kg were used in a complete randomized design. Diets were formulated such that cassava peels was replaced with Gmelina arborea leaf meal at 0, 33.33, 66.67, 100% levels, designated as diets A, B, C, and D respectively. Diet without Gmelina arborea leaf meal was tagged the control diet. The concentrate feed was compounded to contain 16% CP. Diets with 33.33% inclusion level of Gmelina arborea had significantly (P